A novel green corrosion inhibitor extracted from waste feverfew root for carbon steel in H2SO4 solution - Zhou, Zongyi; Min, Xuehong; Wan, Shan; Liu, Jinhang; Liao, Bokai; Guo, Xingpeng (Results in engineering, 2023)
The extract of waste feverfew root (FRE) is firstly used as green corrosion inhibitors for carbon steel in H2SO4 solution. Weight loss method and electrochemical tests are carried out to evaluate the corrosion inhibition efficiency. The in-situ scanning vibrating electrode technique is applied to monitor the inhibitive behavior of corrosion inhibitor. Water contact angle, scanning electron micrograph and X-ray photoelectron spectroscopy are used to characterize the compositions and microstructure of corrosion products. Results indicate that the optimum corrosion inhibition can reach 98.1% at 400 mg/L, and it can retain above 91% after immersion for 96 h. Based on the adsorption isotherm calculation, FRE and KI obey to Langmuir adsorption model. The adsorption film possesses hydrophobicity and can effectively retard the evasion of corrosive media. •The optimum corrosion inhibition efficiency of waste feverfew root (FRE) can reach 98.1%.•Inhibition efficiency retains above 91% after 96 h immersion test.•The adsorption behavior obeys to Langmuir adsorption model.